Pico-hydro Electrification from Rainwater’s Gravitational Force for Urban Area - M Faizal Yaakub; M Farriz Basar; F Hanim Mohd Noh; Hambali Boejang (Universitas Ahmad Dahlan, 2018)
The demand for electrical energy is increasing in most areas in the world. Unstable fossil fuel price and its rapid depletion have led to an intensive research on new energy source and energy conversion. This paper presents the performance of the energy harvesting which focuses on the experimental work to emulate energy harvesting from the rainwater by utilizing a Pico - hydro approach installed to a high building. NACuM core DB-370F DC generators, 1000 litres water tank, 0.5 inch diameter piping system used in two different configurations with three different head setups. The result shows a huge energy harvesting potential obtained from the system and rainwater with maximum 261 milliwatts despite the hardware’s limitation in the setup. Hance, contributes to the cost-efficient due to its small in size, environmentally friendly, and hassle-free maintenance.